Muckle-Wells Syndrome Across Four Generations in One Czech Family: Natural Course of the Disease - Fingerhutová, Šárka; Fráňová, Jana; Hlaváčková, Eva; Jančová, Eva; Procházková, Leona; Beránková, Kamila; Tesařová, Markéta; Honsová, Eva; Doležalová, Pavla (Frontiers in Immunology, 2019)
Background Muckle-Wells syndrome (MWS) represents a moderate phenotype of cryopyrinopathies. Sensorineural hearing loss and AA amyloidosis belong to the most severe manifestations of uncontrolled disease. Simultaneous discovery of MWS in four generations of one large kindred has enabled us to document natural evolution of untreated disease and their response to targeted therapy. Methods A retrospective case study, clinical assessment at the time of diagnosis and 2-year prospective follow-up using standardised disease assessments were combined. Results Collaborative effort of primary care physicians and paediatric and adult specialists led to identification of 11 individuals with MWS within one family. Presence of p.Ala441Val mutation was confirmed. The mildest phenotype of young children suffering with recurrent rash surprised by normal blood tests and absence of fevers. Young adults all presented with fevers, rash, conjunctivitis and arthralgia/arthritis with raised infammatory markers. Two patients aged over 50 years suffered with hearing loss and AA amyloidosis. IL-1 blockade induced disease remission in all individuals while hearing mildly improved or remained stable in affected patients as did renal function in one surviving individual with amyloidosis. Conclusions We have shown that severity of MWS symptoms gradually increased with age towards distinct generation-specific phenotypes. A uniform trajectory of disease evolution has encouraged us to postpone institution of IL-1 blockade in affected oligosymptomatic children. This report illustrates importance of close interdisciplinary collaboration.